Distortion of the Ionization Cross Section of He by the Coherence Properties of a C6+ Beam - Navarrete, Francisco; Barrachina, Raúl; Ciappina, Marcelo F. (My University, 2019)
We analyze the influence of the coherence of the projectile’s beam in scattering phenomena. We focus our study in the ionization of He byC6 +projectiles at 100 MeV/amu. We assess the influence of this effect by performing a Born initial state and continuum distorted wave final state (CDW-B1) calculation together with a rigorous procedure to account for the initial coherence properties of the projectile’s beam. These calculations, which had been previously performed for only the scattering and perpendicular collision planes and within the First Born approximation (FBA), were repeated for an ampler set of collision planes. Additionally, a more refined method to describe the applicability of the aforementioned procedure, is used. We achieve a better qualitative agreement with the experimental results.
Keywords: coherence; ionization; collisions; linearly polarized intense infrared